Revision of the species related to Lalagetes subfasciatus Boheman and transfer of remaining Lalagetes species to other genera of Embrithini (Coleoptera: Curculionidae: Entiminae) - Borovec, Roman; Skuhrovec, Jiří (Zootaxa, 2018)
The genus Lalagetes Schoenherr, 1842 is redefined, compared with related genera and all known species placed among three genera. Four new species from South Africa are described: L. andersoni sp. nov. (Mpumalanga), L. howdenorum sp. nov. (Limpopo), L. sarkae sp. nov. (KwaZulu-Natal) and L. zitae sp. nov. (KwaZulu-Natal). Lectotypes of Lalagetes seminulum Fåhraeus, 1871 and L. subfasciatus Boheman, 1842 are designated here, and both species redescribed. All of the following species are keyed and illustrated. The following new combinations are proposed: Glyptosomus edax (Marshall, 1939), G. inaequalis (Marshall, 1941), G. leurops (Marshall, 1931), G. setosus (Boheman, 1845), G. squamulatus (Boheman, 1842), G. subfrenatus (Marshall, 1947b), G. variegatus (Boheman, 1845), Phaylomerinthus hispidus (Hartmann, 1906), P. nanus (Marshall, 1947a), P. pallipes (Fåhraeus, 1871), P. parcus (Marshall, 1947a), P. rudis (Marshall, 1958), P. signatus (Hartmann, 1906) and P. viridulus (Fåhraeus, 1871).